Phase imaging dislocations using diffracted beam interferometry. (2nd December 2020) - Herring, Rodney
Abstract: A phase imaging method that measures the phase shift existing at a dislocation's core is described. The method uses the interference of two symmetrically diffracted beams on the optic axis by means of an electron biprism. Each diffracted beam carries half the phase of the dislocation core. When combined, the entire phase shift of the dislocation core is obtained.